The Global Competitive Situation and Strategy of Space Frequency and Orbit Resources - Feng LAN; Zhaoqi PENG (天地一体化信息网络)
Combined with ITU Radio Rules and the actual in-orbit satellites situation, the satellite communication frequency resource allocation, the regulation and the use of orbital positions were analyzed, the planning and frequency-orbit resources of the international mainstream low-orbit internet constellations were expounded, and the satellite networks information on China's low-orbit constellation was listed.For the development of low-orbit internet constellations, it was proposed that China's low-orbit internet constellations should be based on China's national conditions, the new technologies and frequency bands should be used, to resolve the frequency resources bottleneck.